Pot-pollen DNA barcoding as a tool to determine the diversity of plant species visited by Ecuadorian stingless bees - Joseline Sofía Ocaña-Cabrera; Sarah Martin-Solano; Jorge Ron-Román; Jose Rivas; Mutien-Marie Garigliany; Claude Saegerman (PLoS ONE, 2025)
Identifying the main species of plants from where Ecuadorian stingless bees collect pollen is one of the key objectives of management and conservation improvement for these insects. This study aims to determine the botanical origin of pot-pollen using two barcodes, comparing two methodologies (DNA barcoding versus electron microscopy and morphometric tools) and determine the genus and species of pollen source plants of the main honey-producing stingless bees in Ecuador. As main results, Prockia crucis, Coffea canephora, Miconia nervosa, Miconia notabilis, Laurus nobilis, Cecropia ficifolia, Theobroma sp., Artocarpus sp., Croton sp., Euphorbia sp., Mikania sp., and Ophryosporus sp., were the genera and species with the highest presence in the nests (n = 35) of three genera of stingless bees of two provinces located in different climatic regions inside the continental Ecuador. Plant species richness in both areas was statistically similar (p-value = 0.21). We concluded that floral sources’ molecular identification with the ITS2 region had a higher number of genera and species detected, than the rbcL gene and microscopy tools, for the Ecuadorian landscapes. We confirmed that the foraging behavior of Melipona sp., Scaptotrigona sp., and Tetragonisca sp., could include non-native flora (27%, 12/44 identifications) that provide a rich source of pollen. Stingless beekeepers could use this information to create flower calendars and establish a schedule for better management of stingless bees in secondary and modified environments.